TINGKAT INTEGRITAS PERANAN NEGARA DAN KEUANGAN PUBLIK INDONESIA DALAM PEMIKIRAN IMAM AL-GHAZALI - Rofika Febriani; Siti Nur Azizah (AL-KHARAJ, 2021)
AbstractThis article discusses the level of integrity of the role of the state and public finances in Indonesia according to Imam Al-Ghazali's thoughts. From the discussion of this article, it is found that, First; aspects of the source of state revenue are considered not fully appropriate, namely in Imam Al-Ghazali's thinking there are taxes while in Indonesia there are none, taxes are imposed on non-Muslims in the form of ghanimah, fa'i, jizyah, and tribute while in Indonesia taxes are imposed on all Indonesian citizens. or who work in Indonesia, Imam Al-Ghazali's debt acquisition (loan) requires that it is possible to guarantee the repayment of future income while in Indonesia the loan cannot be paid and continues to accumulate. Bank Indonesia (BI) noted that Indonesia's foreign debt in August 2020 reached 413.4 billion US dollars (equivalent to Rp. 6,076.9 trillion). Second; In terms of sources of state expenditure, it is considered not entirely appropriate, namely in Imam Al-Ghazali's thinking that the distribution of state revenue (expenditure) must be efficient and must not be wasteful, while in Indonesia several programs funded by the government are still deemed inefficient. The government has been too wasteful in implementing the state budget for the last 4 years (in 2019), this is evident from the significant increase in the budget for goods expenditures, the Central Government Financial Report (LKPP) reports an increase in capital expenditure reaching 51.97% in a period of four years. Most recently, in 2015-2019, personnel expenditure increased from 200 trillion to around 300 trillion. Then the level of integrity of the role of the state and public finances in Indonesia according to the thought of Imam Al-Ghazali also wrote an estimate of 79%, AbstrakArtikel ini membahas tentang tingkat integritas peranan negara dan keuangan publik di Indonesia menurut pemikiran Imam Al-Ghazali. dari pembahasan artikel ini didapatkan pemahaman bahwa, Pertama; aspek sumber penerimaan negara dinilai belum sepenuhnya sesuai, yaitu dalam pemikiran Imam Al-Ghazali ada pajak sedangkan di Indonesia tidak ada, pajak dibebankan untuk non muslim berupa ghanimah, fa’i,  jizyah, dan upeti sedangkan di Indonesia pajak dikenakan untuk semua warga negara Indonesia atau yang bekerja di Indonesia, pembolehan utang (pinjaman) imam Al-Ghazali mensyarakan harus memungkinkan untuk menjamin pembayaran kembali dari pendapatan di masa yang akan datang sedangkan di Indonesia pinjaman belum dapat dibayarkan dan terus menumpuk. Bank Indoneisa (BI) mencatat utang luar negeri Indonesia pada agustus 2020 mencapai 413.4 miliar dollar AS (setara dengan Rp. 6.076.9 triliun). Kedua; aspek  sumber pengeluaran negara, dinilai belum sepenuhnya sesuai, yaitu dalam pemikiran Imam Al-Ghazali penyaluran pendapatan negara (pengeluaran) harus efisiensi dan tidak boleh bersikap boros sedangkan di Indonesia beberapa program yang yang dibiayai pemerintah masih dirasa kurang efisien. Pemerintah dinali terlalu boros dalam melaksanakan APBN selama 4 tahun terakhir ini (di tahun 2019), hal tersebut terbukti dari kenaikan anggaran belanja barang yang signifikan, Laporan Keuangan Pemerintah Pusat (LKPP) melaporkan peningkatan belanja modal mencapai 51.97% dalam kurun waktu empat tahun. terkahir tercatat pada tahun 2015-2019 belanja pegawai naik dari 200 triliun menjadi sekitar 300 triliun. Kemudian tingkat integritas peranan negara dan keuangan publik di Indonesia menurut pemikiran Imam Al-Ghazali penulis angkakan senilai 79%,